Beyond the Spirometry: New Diagnostic Modalities in Chronic Obstructive Pulmonary Disease - Jin Hwa Song; Youlim Kim (Tuberculosis and Respiratory Diseases)
Spirometry can play a critical role as a gold standard in the diagnosis and treatment of patients with chronic obstructive pulmonary disease (COPD). While the criteria for diagnosis have advanced over time, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) standard of the forced expiratory volume in 1 second/forced vital capacity ratio <0.7 remains the most universally employed metric. However, spirometry cannot be utilized in all situations, and test execution can be difficult for some patients, often showing normal values in the early diagnosis of COPD. Therefore, research on new diagnostic methods is underway. Techniques include whole-body plethysmography for measurement of residual volume and inspiratory capacity and airway resistance, diffusing capacity of carbon monoxide or nitric oxide, impulse oscillometry, infrared time-offlight depth image sensor, diaphragm ultrasonography, which can enable early diagnosis and multifaceted assessment of patients with COPD.